Nonmelanoma Skin Cancer at Critical Facial Sites: Results and Strategies of the Surgical Treatment of 102 Patients - Carlos Alberto Ferreira de Freitas; Andreza Negreli Santos; Guilherme Canho Bittner; Baltazar Dias Sanabria; Maria Margarida Morena Domingos Levenhagen; Günther Hans-Filho (Journal of Skin Cancer)
Background. To evaluate the surgical treatment results of a consecutive series of patients with nonmelanoma skin cancer in critical facial regions such as the nose, lip, eyelid, ear, forehead, cheek, and chin. Methods. This was a prospective observational cohort study evaluating the surgical treatment results of 102 patients with nonmelanoma skin cancer who underwent surgical excision and required some type of reconstruction. The reconstruction strategy used, histological type and margins, aesthetic result, and complications were evaluated. Results. The most common facial site was the nose (48.01%), followed by the eyelid, ear, cheek, forehead, and lip. The most frequently used type of reconstruction was the advancement flap (30.39%), followed by transposition flap (27,45%), rotation flap (14.70%), and grafts (10.78%). Basal cell carcinoma was the most frequent histological type, accounting for 90.19% of the sample, with 54.90% of these cases being of the nodular subtype. Disease-free margins were obtained in 94.11% of the patients, and only one patient presented compromised margins and underwent marginal extension. A good cosmetic result was found in 93.13% of the participants. Conclusion. Surgical treatment can provide excellent oncological, functional, and cosmetic results in the treatment of patients with nonmelanoma skin cancer at critical facial sites.